Oxytocin and the stress buffering effect of social company: a genetic study in daily life. Issue 3 (16th March 2020) - Sicorello, Maurizio; Dieckmann, Linda; Moser, Dirk; Lux, Vanessa; Luhmann, Maike; Schlotz, Wolff; Kumsta, Robert
Abstract: Social relationships are a crucial determinant of both mental and physical health. This effect is partly due to social buffering of stress. Animal studies suggest that social buffering is mediated via the oxytocin system, while studies in humans are sparse and limited by the low ecological validity of laboratory settings. In the present study, participants ( N  = 326) completed smartphone questionnaires four times a day over 4 to 5 days, measuring stressors, negative affect, and social context to assess social buffering. We found that under stress, participants reported a higher need for social company. Further, the impact of prior stressful events on momentary negative affect was attenuated by the perceived pleasantness of current social company. This social buffering effect was moderated by haplotypes of the oxytocin receptor gene, based on two well-described single nucleotide polymorphisms (rs2268498, rs53576). Effects were robust when controlling for gender and age, applying different data quality criteria, and even apparent in genotype-based analyses. Our findings demonstrate that social buffering and its modulation by oxytocin system characteristics have implications for life as lived outside the laboratory.